Cutaneous silent period in human immunodeficiency virus-related peripheral neuropathy - Osio, Maurizio; Zampini, Luisa; Muscia, Francesco; Valsecchi, Laura; Comi, Cristoforo; Cargnel, Antonietta; Mariani, Claudio (Journal of the peripheral nervous system, 2004)
The aim of this work was first to determine whether the cutaneous silent period (CSP), a marker of small‐nerve‐fibre function, was altered in human immunodeficiency virus (HIV)‐positive subjects with predominantly sensory symmetrical polyneuropathy and, second, to assess whether such alterations were predictive of an impairment in the largest calibre sensory and motor nerve fibres of the upper limb (UL) peripheral nerves. CSP was assessed in three groups of subjects: healthy control subjects, HIV‐positive subjects with peripheral neuropathy (PN) of the lower limbs, and HIV‐positive patients with clinical and neurophysiological involvement of the four limbs. CSP study showed a significant increase of the latency compared to the controls both in HIV‐positive cases with no impairment in the UL (p = 0.006) and in patients with four‐limb neuropathy (p = 0.002). CSP study in HIV‐positive patients with mild lower limb distal sensory polyneuropathy can detect an early involvement of the UL peripheral nerves. CSP latency increase could therefore be addressed as the first sign of PN spreading to the UL.